The effects of life review structured program on the life satisfaction of elderly Chinese women - Lin, Theresa (Sr. Lim Jam Huang), PSC (Animo Repository, 1996)
This study dwells on the effects of a Life Review Structured Program on the Life Satisfaction of five Chinese elderly women. It was based on the theory of Erikson which posited a psycho-social development task at the late adulthood stage of integrity vs. despair and a continuity of life situations such that previous life experiences impact ego development in the next stage. The Life Review Program (LRP) revolved around this process of reminiscing past experiences to connect with the present life satisfaction. The study focused on the life satisfaction of the elderly Chinese women in terms of overall life satisfaction, and 7 dimensions before and after undergoing a Life Review Program. The dimensions included (1) health, (2) economic security, (3) acceptance by society, (4) feeling of usefulness, (5) contentment, (6) freedom from loneliness, and (7) religion. Only three of the respondents actually went through the LRP. One was visited while the other was not visited whatsoever. This was deliberately done for control and comparison purposes. Life Satisfaction was measured through the 5-Step Ladder Scale and the 5-Point Life Satisfaction Scale. The LRP included structured techniques of looking at photo albums, listening to music, and either storytelling of verbal autobiography. The actual program consisted of five sessions. Guide questions were provided to facilitate the process. The study also explored significant life experiences in terms of happiest and loneliest moments and the happiest and loneliest moments cited by the subjects during the LRP. Interviews with family members were conducted to confirm and validate the effects of the LRP as indicated by the test results. Data showed that in general, the LRP helped the elderly women improve their level of life satisfaction. The satisfaction was manifested in terms of greater self-acceptance, more awareness of one's individuality and uniqueness, and a positive attitude towards death. Although sometimes experiencing feelings of loneliness and increased discontentment in some instances, the elderly subjects as a whole, managed to sustain a moderate level of life satisfaction, more happiness, and feeling of pride in their accomplishments. Significant life experiences in the past cited and connected to one's present feeling of satisfaction were in the areas of family relationship and roles or functions in society. Results also showed that changes occurring in life satisfaction may be brought about by natural circumstances beyond the control of the counselor-researcher and the LRP. For the control subjects, changes appeared to be toward either more gaps between present and desired conditions or more life dissatisfaction because LRP was not applied.